PERILAKU HIDUP SEHAT DAN PRESTASI BELAJAR SISWA SEKOLAH DASAR - Abdul Rahmat; Mardia Bin Smith; Maryam Rahim (Psympathic : Jurnal Ilmiah Psikologi, 2015)
Healthy life behavior amongst primary school students need to be reviewed concerning that healthy behavior at primary school age as a basic foundation for the healthy growth and development. Growth and healthy development would be enabling conditions for a variety of children's activities, including learning. This research aimed to grasp an overview of the correlation between health behavior and academic achievement of students. This research design was correlational with a sample size of 30 students. Based on the analysis of data, there is a significant correlation between health behavior and academic achievement of students. In this case the better the health behavior of students, the better the academic achievement.